Fuzzy Logic Controller For Depth Control Of Underwater Remotely Operated Vehicle - Mohd Shahrieel, Mohd Aras; Shahrum Shah, Abdullah; Siti Yasmin, Othman; Marizan, Sulaiman; Mohd Farriz, Md Basar; Mohd Khairi, Mohd Zambri; Muhammad Nizam, Kamarudin (JATIT & LLS, 2016)
Nowadays, unmanned underwater vehicle (UUV) is created to reduce human intervention in deep-water application. UUV can help human to make an underwater application that commonly used in deep water industries. During operation, the UUV undergoes a complex multi-axis motion trajectories that are highly nonlinear because the subsystems in the UUV are ill-defined and strongly coupled to each other. The conventional controller such as Proportional, Integral and Derivative (PID) and Proportional and Derivative (PD) have a problem to control nonlinear operation. The conventional controller hardly to achieve zero overshoot. Implementation of the controller on the UUV using Fuzzy Logic Controller (FLC) itself poses its own level of complexity. Consequently, implementation of FLC also requires fast and high-performance processors. The objectives of this paper are to study the effect of the tuning membership function to improved performances of the FLC for depth control using actual underwater Remotely Operated Vehicle (ROV) based on VideoRay ROV Pro III as well as to analyze performance of system response of depth control in terms of zero overshoot, faster rise time and small steady state error. Then, the proposed approach is verified using hardware interfacing between MATLAB/Simulink and Microbox 2000/2000C. The result shows FLC gives rather best performance in term of faster rise time, zero overshoot and small steady state error as compared with conventional controllers.